First-Order Resolution
- In general
- Find a literal L1 from clause C1, L2 from clause C2, and
substitution θ such that L1 θ = ¬ L2
θ.
- Form the resolvent C by including all literals from
C1θ and C2θ, except for L1θ and
¬L2θ. More precisely, the set of literals occurring in the conclusion C is
C = (C1 - {L1})θ ∪(C2 - {L2})θ
- That is, θ is a unifying substitution for L1 and
¬ L2.
- For example, let C1 = White(x) ← Swan(x) and C2 =
Swan(Fred).
C1 can be re-written as White(x) ∨ ¬ Swan(x)
Then L1 = ¬ Swan(x), L2 = Swan(Fred) if θ ={x/Fred}
So C = White(Fred).
José M. Vidal
.
42 of 47